The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/pr7090560
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Swine Manure into Hydrochars

Abstract: There is a significant interest in valorizing swine manure that is produced in enormous quantities. Therefore, considering the high moisture content in swine manure, the objective of this research was to convert manure slurry into hydrochars via hydrothermal carbonization and analyze the yields, pH, energy contents, and thermal and oxidation kinetic parameters. Experiments were performed in triplicate in 250 mL kettle reactors lined with polypropylene at 180 °C, 200 °C, 240 °C, 220 °C, and 260 °C for 24 h. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…It is also used for active air and water filtration given its effective binding to heavy metals. [90][91][92] The abundant nutrients in manure ( phosphorus, nitrogen, potassium, sulphur) 93 make this biowaste a water and solid contaminant when inappropriately managed. Therefore, it is necessary to provide efficient recycling or upcycling approaches to profit from the 73 million tons of manure produced each year in the United States alone.…”
Section: Terrestrial Animal Originmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also used for active air and water filtration given its effective binding to heavy metals. [90][91][92] The abundant nutrients in manure ( phosphorus, nitrogen, potassium, sulphur) 93 make this biowaste a water and solid contaminant when inappropriately managed. Therefore, it is necessary to provide efficient recycling or upcycling approaches to profit from the 73 million tons of manure produced each year in the United States alone.…”
Section: Terrestrial Animal Originmentioning
confidence: 99%
“…94 Swine manure has potential for hydrochars via hydrothermal carbonization. 93 These carbon structures are used for energy storage or soil/water remediation purposes. The high cellulose content of (elephant) manure could be exploited to obtain nanocellulose through an energy-efficient approach profiting from the cellulose already attacked by animal acid and enzymes.…”
Section: Organic Waste Feedstockmentioning
confidence: 99%
“…Similar to pyrolysis, the carbon content of biomass is increased while oxygen and hydrogen contents are decreased, thus resulting in a higher energy-dense hydrochar. The produced hydrochar has improved fuel properties such as high calorific value, high carbon content, high degree of homogeneity, low degradability, hydrophobicity, better self-binding properties, etc., and it is comparable to bituminous or lignite coal (Baratieri et al, 2015;Lentz et al, 2019). However, the distribution, composition, and structure of HTC products, including the properties of hydrochar (HHV, porosity, moisture content, etc.…”
Section: Htc Processmentioning
confidence: 99%
“…Moreover, HTC allows recovering valuable chemicals and nutrients from waste biomass. Some studies (Liu et al, 2017b;Lentz et al, 2019) claim hydrochar has more developed porosity than biochar, making it more suitable for soil remediation, enrichment, and carbon sequestration. Further, Gascó et al (2018) reported that HTC could concentrate phosphorus and heavy metals in hydrochar.…”
Section: Htc Processmentioning
confidence: 99%
“…HTC was first studied by Nobel laureate Friedrich Bergius (1913), who described the process of carbonization in a few hours by means of high temperature and self-generated pressure . In recent years, HTC technology has received growing attention at lab and pilot-plant scale, and a number of full-scale projects have been developed with different biomass wastes, such as sewage sludge, animal manure, ,, biowaste, , lignocellulosic biomass and mixed residues. Some pilot-scale HTC plants have been constructed (Ingelia, HTCycle, Terranova Energy, Ava CO 2 ), but thus far, the detailed structure of such plants and their efficiencies are still unknown to most researchers involved in HTC.…”
Section: Introductionmentioning
confidence: 99%